RELATIONSHIP BETWEEN BIG FIVE PERSONALITY TYPES AND INTERPERSONAL COMMUNICATION WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN EMPLOYEES OF PT. TRIMINDO JAYA MANDIRI - Dhiya Astari; Nina Siti Salmaniah Siregar; Patisina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the relationship between the support of the big five personality types and Interpersonal Communication on Organizational Citizenship Behavior at PT. Trimindo Jaya Mandiri, with a research sample of 180 employees. The method used in this study is a quantitative method with a sampling technique using the Total Sampling Technique. The instrument used is a Likert scale model questionnaire. The analysis technique used is Multiple Regression. Based on the results of the study it was concluded that: 1) There issignificant positive relationship between big five personality on organizational citizenship behavior of employees of PT. Trimindo Jaya Mandiri, with a predictor determinant coefficient value () of 0.348 which means that the big five personality contributes 34.8% to influencing organizational citizenship behavior. This means that the higher the big five personality, the higher the organizational citizenship behavior. Conversely, the lower the big five personality, the lower the organizational citizenship behavior. 2) Existencesignificant positive relationship between interpersonal communication on organizational citizenship behavior of employees of PT. Trimindo Jaya Mandiri, with a predictor determinant coefficient value () of 0.384 which means interpersonal communication contributes 38.4% to organizational citizenship behavior. This means that the higher the interpersonal communication, the higher the organizational citizenship behavior. Conversely, the lower the interpersonal communication, the lower the organizational citizenship behavior. 3) ExistenceThere is a significant positive relationship between big five personality and interpersonal communication on organizational citizenship behavior of employees of PT. Trimindo Jaya Mandiri, with a predictor determinant coefficient value () of 0.423 which means that big five personalities and interpersonal communication contribute 42.3% to influencing organizational citizenship behavior.